PENGARUH PENAMBAHAN DOSIS CEMENT GRINDING AID (CGA) TERHADAP SETTING TIME DAN KUAT TEKAN MORTAR PADA SEMEN PCC DI PT. SEMEN BATURAJA TBK - Sunarsih, Tri; Marzuki, Hasan; Anaser, Novadri; Safaruddin, Safaruddin (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Cement Grinding Aid (CGA) appears as an addition that has the potential to affect the characteristics of the mortar in PCC cement. The purpose of this study is to optimize the formulation of PCC cement from CGA-MBS and CGA-MAPEI types against the Setting Time and mortar compressive strength. In this study, a physical test method was used, namely the setting time and mortar compressive strength test. From the results of the study, the setting time test is faster for the CGA-MAPEI type because it increases the smoothness of the cement, while the CGA-MBS type has a chemical composition content that more affects its properties as a more stable and resistant adhesive. In the mortar compressive strength test, the addition of a dose of CGA (100 – 400) ppm the compressive strength value of CGA-MAPEI mortar is higher than that of GCA-MBS, but in the addition of a dose of 500 ppm, the compressive strength value of CGA-MAPEI is still below the compressive strength value of CGA-MBS.